The Effects of Attention-Deficit/Hyperactivity Disorder on Employment and Household Income - Biederman, Joseph (Medscape, 2006)
CONTEXT: Many children with attention-deficit/hyperactivity disorder (ADHD) continue to exhibit symptoms of the disorder into adolescence and adulthood. Although ADHD may have a profound impact on activities of daily living, including educational achievement and work performance, limited research exists on ADHD's impact on individual income loss and overall economic effect. OBJECTIVES: Evaluate ADHD's impact on individual employment and income, and quantify costs of ADHD on workforce productivity for the US population. DESIGN: Two telephone surveys were conducted between April 18, 2003, and May 11, 2003, to collect demographic, educational, employment, and income information. PARTICIPANTS: Two groups of adults aged 18-64 years were interviewed: those diagnosed with ADHD (n = 500) derived from a national list of mail-paneled members who identified themselves or a household member as having been diagnosed with ADHD, and an age- and gender-matched control group (n = 501) derived from a random digital-dialing sample of a national cross-section not diagnosed with ADHD. RESULTS: Statistically fewer subjects in the ADHD group achieved academic milestones beyond some high school (P < .05). In addition, fewer subjects with ADHD were employed full time (34%) compared with controls (59%; P < .001). Except for the subgroup of subjects aged 18-24 years, average household incomes were significantly lower among individuals with ADHD compared with controls, regardless of academic achievement or personal characteristics. On the basis of these findings, loss of workforce productivity associated with ADHD was estimated between $67 billion and $116 billion. CONCLUSIONS: Decreased individual income among adults with ADHD contributes to substantial loss in US workforce productivity.